2013
DOI: 10.1016/j.vaccine.2013.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Impact of rotavirus vaccine on rotavirus genotypes and caliciviruses circulating in French cattle

Abstract: Group A rotaviruses are a leading cause of neonatal calf diarrhoea worldwide and prevention of this disease includes vaccination against these viruses. In order to highlight the potential selection of rotavirus genotypes due to immune pressure driven by vaccination, the aim of this study was to compare group A rotavirus genotypes circulating in French diarrhoeic calves in rotavirus vaccinated herds (G6P[5] vaccine) with those in non-vaccinated herds during one calving season in 2010. This study showed a high p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 31 publications
2
20
0
2
Order By: Relevance
“…Both genotypes are widely distributed among diarrheic and healthy cattle, juveniles, and adults, although GIII.2 viruses have been found more frequently than GIII.1. The majority of published surveys has tested diarrheic calves, in which bovine norovirus was frequently found [13,42,50,51,63,69,71,72,78,79,91,92,100,102,109,115,116]. One case–control study that investigated pathogens associated with calf diarrhea in the USA tested 444 samples of 1–2 week-old diarrheic and asymptomatic calves for a panel of 11 enteric pathogens (bacteria and viruses) using real-time RT-PCR with bovine norovirus specific probes.…”
Section: Resultsmentioning
confidence: 99%
“…Both genotypes are widely distributed among diarrheic and healthy cattle, juveniles, and adults, although GIII.2 viruses have been found more frequently than GIII.1. The majority of published surveys has tested diarrheic calves, in which bovine norovirus was frequently found [13,42,50,51,63,69,71,72,78,79,91,92,100,102,109,115,116]. One case–control study that investigated pathogens associated with calf diarrhea in the USA tested 444 samples of 1–2 week-old diarrheic and asymptomatic calves for a panel of 11 enteric pathogens (bacteria and viruses) using real-time RT-PCR with bovine norovirus specific probes.…”
Section: Resultsmentioning
confidence: 99%
“…G6, G8, G10 are the most predominant G types in bovines P[1], P[5] and P[11] have been recorded in the majority of bovine diarrhoeal cases [4,5]. Previous studies in Ireland have indicated that genotypes G6 and G10 in various combinations with P genotypes P[1], P[5] and P[11] were the only circulating genotypes in the Irish bovine population [6,7].…”
Section: Resultsmentioning
confidence: 99%
“…General recommendations regarding decrease of RVA diarrhea include management practices, especially good hygiene and sanitation procedures, as well as pathogen-specific interventions, such as the use of vaccine prophylaxis (Alkan et al 2010;Izzo et al 2011). The vaccination of cows aims an increase of the concentration of specific antibodies in colostrum against targeted pathogens (Kaplon et al 2013). Although many reports state that vaccination programs of pregnant cows are one of the main strategies for prevention of RVA diarrhea in calves, it must be kept in mind that calves that receive a sufficient quantity of specific antibodies through colostrum intake are not completely protected against rotavirus infection, instead, the severity of clinical signs is decreased, reducing deaths from RVA infection (Parreño et al 2004;Kaplon et al 2013).…”
Section: Introductionmentioning
confidence: 99%